The Role of Virtual Reality to Enhance Learning Motivation: A Bibliometric Analysis - Ronny Trian Surbakti (Westscience Press, 2024)
The rapid advancement of virtual reality (VR) technology has sparked interest in its potential use in educational settings. This study investigates how virtual reality could enhance learning motivation using a bibliometric analysis of scholarly works published between 2020 and 2024. The primary objectives are to identify significant research trends, notable works, and emerging subjects in the literature. 300 relevant articles were collected from Scopus, which served as the data source. The analysis was done using bibliometric tools such as VOS viewer. The study focused on co-authorship networks, citation patterns, and phrase co-occurrence in order to map the research landscape. The results demonstrate that interest in VR's potential to raise learning motivation is growing, with interdisciplinary collaborations at foreign institutions playing a significant role in this trend. The significance of integrating technology, creating immersive learning environments, and the psychological impacts of virtual reality on student engagement are highlighted in important findings. Despite the positive advancements, accessibility issues and constraints in long-term impact research were discovered. This research contributes to the body of knowledge currently in existence and offers useful information for academics, educators, and policymakers with its in-depth examination of Virtual Reality's effect on educational motivation. More research is required to close the gaps observed to fully realize the potential of virtual reality in education.